2016
DOI: 10.1111/cge.12714
|View full text |Cite|
|
Sign up to set email alerts
|

Application of whole‐exome sequencing for detecting copy number variants in CMT1A/HNPP

Abstract: Large insertions and deletions (indels), including copy number variations (CNVs), are commonly seen in many diseases. Standard approaches for indel detection rely on well-established methods such as qPCR or short tandem repeat (STR) markers. Recently, a number of tools for CNV detection based on next-generation sequencing (NGS) data have also been developed; however, use of these methods is limited. Here, we used whole-exome sequencing (WES) in patients previously diagnosed with CMT1A or HNPP using STR markers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Recent studies used different analysis tools of WES data aiming to obtain some initial information regarding the possibility of CNV occurrence at multiple known loci 28 29. The analyses are based on coverage data of specific genomic regions, which need to be at a minimal quality to ensure reliability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies used different analysis tools of WES data aiming to obtain some initial information regarding the possibility of CNV occurrence at multiple known loci 28 29. The analyses are based on coverage data of specific genomic regions, which need to be at a minimal quality to ensure reliability.…”
Section: Discussionmentioning
confidence: 99%
“…A few WES-based approaches have been developed for CNV detection including ExomeCNV,30 CONIFER31 and CEQer 32. Although developed for detecting CNVs at a genomic view, these tools were reported to be applicable mainly in targeted analysis of a specific genomic locus and were reported to indeed yield reliable results 29. The most challenging task of these tools is to effectively filter out false-positive CNVs when analysing a large set of data with no previous knowledge of the deletion location.…”
Section: Discussionmentioning
confidence: 99%
“…The technique has the potential to detect CNVs in the coding regions of genes at an exon level resolution, which is not always feasible when using traditional CGH and MLPA approaches [Gambin et al, 2016]. Only within the last year has WES successfully been able to detect CNVs in other human disease studies with acceptable reliability [Gambin et al, 2016;Jo et al, 2016], although the precision of the data analysis pipelines is currently less than 80% when comparing large cohorts [Gambin et al, 2016]. Recently a study using WES to screen 2,603 patients with a range of genetic disorders, including 38 DSD patients, showed that on average each patient had 6 CNVs throughout their genome [Pfundt et al, 2017].…”
Section: Massively Parallel Sequencing Technologies: New Methods To Imentioning
confidence: 99%
“…To date, diagnostic algorithms for CMT1 have proposed using multiplex ligation probe amplification (MLPA) for the detection of duplications and deletions of the short arm of chromosome 17 before proceeding to disease-specific panels or WES [2]. In a small sample of three patients with CMT1A, Jo and colleagues were able to identify both duplications and deletions in chromosome 17p using WES suggesting that NGS may eventually supersede the need for MLPA for diagnosing CMT1A [6]. …”
Section: Introductionmentioning
confidence: 99%